Performance analysis of an irreversible Brayton heat engine based on ecological coefficient of performance criterion - Sahin, Bahri; Ust, Y.; Kodal, A. (Elsevier BV, 2006)
A performance optimization based on a new ecological criterion called ecological coefficient of performance (ECOP) has been presented for irreversible Brayton heat engine. The considered model includes irreversibilities due to finite rate heat transfer, heat leakage and internal dissipations. The ECOP objective function is defined as the ratio of power output to the loss rate of availability. The optimal performance and design parameters at maximum ECOP conditions are obtained analytically. The effects of major parameters on the general and optimal ecological performances have been investigated. The obtained results based on ECOP criterion are compared with an alternative ecological objective function defined in the literature and the maximum power output conditions, in terms of entropy generation rate, thermal efficiency and power output.